Robust control of nonlinear time-varying mismatched uncertain systems - Wang, Wei Hua. (2010)
This thesis is concerned with the problem of robust control (robust output tracking and robust stabilization)for multi-input multi-output (MIMO)nonlinear systems with time-varying mismatched uncertainties. State feedback linearization of in-put/output (I/O)map will be assumed for the nominal system and the control design combines differential geometric feedback linearization with the determin-istic approach, in which no statistical property of the uncertainties is assumed. With the knowledge of the bounds of the uncertainties, we first generalize the Stable Combined Variable Perturbation Method which was first proposed by Li et al. [20-23] for SISO nonlinear systems to handle the MIMO case and obtain three new robust tracking controllers. Each of them reduces the effects of arbitrarily-large bounded mismatched uncertainties step by step to achieve robust output tracking. However, knowledge of the uncertainty bounds are not always available, and the conservative estimation of the bound may cause unnecessary large control effort. Therefore, an adaptive robust tracking controller is also derived which does not require the knowledge of the bounds of the uncertainties. The adaptive robust controller is therefore more feasible and practical and can be used to replace the previous non-adaptive ones.